Murder in plain English: from manifestos to memes - looking at murder through the words of killers - Arntfield, Michael (Prometheus Books, 2017)
"This is the first book to examine murder through the written word--not only the writings of the killers themselves, but also the story of murder as told in literary fiction and the crime dramas that are now a staple of film and television. The authors--a criminologist specializing in cold cases, written evidence, and forensic science, and an anthropologist who has dealt with the signs and ciphers of organized crime and street gangs in his previous work--are widely recognized experts in this emerging specialty field. Based on extensive research and interviews with convicted murderers, the book emphasizes the often-overlooked narrative impulse that drives killers, with the authors explaining how both mass and serial murderers perceive their crimes as stories and why a select few are compelled to commit these stories to writing whether before, during, or after their horrific acts. The book also analyzes the written work of killers, using a combination of machine-based linguistic patterning, predictive modeling, and symbolic interpretation, to make sense of the screeds of everyone from the Son of Sam and the Zodiac Killer to the Columbine attackers, the Unabomber, and the recent spate of mass shooters using social media as their preferred narrative platform. They present a theoretical perspective of murder that is based on both the criminological evidence and written works. In addition, the authors examine famous literature that has dealt ingeniously with murder and its relationship with real crime, from the Greek tragedians to Truman Capote to modern-day productions such as Making a Murderer. This unique approach offers a new means to penetrate the minds of murderers, revealing their motives as well as the wider social meanings of this age-old crime and our continuing fascination with it"--